Polarization-Insensitive and Tunable Silicon Mach–Zehnder Wavelength Filters With Flat Transmission Passband - Xiuling Deng; Lianshan Yan; Hengyun Jiang; Xia Feng; Wei Pan; Bin Luo (IEEE Photonics Journal)
In this paper, an integrated polarization-insensitive optical comb filter with flat passband and tunable central wavelength is designed based on cascaded Mach–Zehnder structure. It is realized by employing three specific directional couplers with square waveguides. The central wavelength of the proposed filter for both TE and TM modes can be equally shifted. Simulation results show that the designed filter has a 3-dB bandwidth of 2.8 nm, a free spectral range of 6.09 nm, and a minimum insertion loss of 0.315 and 0.325 dB for TE and TM mode, respectively. Moreover, the polarization-dependent loss is ∼0.05 dB over the passband.